Floral visitors, pollination and floral biology of Tecoma castanifolia (D. Don) Melch. (Bignoniaceae), in two localities of the city of Guayaquil, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2017)
The floral visitors, pollinators, strategies of pollination and floral biology of Tecoma castanifolia (Bignoniaceae) were recorded in two localities at the city of Guayaquil, in coastal Ecuador, from October 2016 to May 2017. T. castanifolia produce events of high flowering synchrony, each of those having an average of 33 days. The flowers are hermaphrodites; those have two systems to induce allogamy: protandry and approach herkogamy. Eighty-nine species, mostly insects, and arachnids and birds, visited the inflorescences of T. castanifolia. The most abundant and frequent visitors are Hymenoptera, those are the most important regarding to pollination. The effective pollinators have sizes ranging from 4 mm (Augochlorella sp.) to 2 cm long. (Eulaema polychroma). The main pollinators are: Euglossa sp., Apis mellifera, and Exomalopsis sp. (all Apidae), those transport 87.68% of pollen grains approximately. Characteristics as the non-obligatory plantpollinator interactions, the wind dispersal method, and the abundance of viable seeds, allows T. castanifolia successfully colonize new areas, even when the most important pollinators from other localities do not occur there. That suggests that the flowers of T. castanifolia are not linked to any specific visitor, and that T. castanifolia is a promissory species for restoration of disturbed habitats in dry forests of coastal Ecuador and NW Peru.
Keywords: Bignoniaceae; Ecuador; pollination; pollinators; floral synchrony; Tecoma castanifolia